RATIONAL REASONING OR ADAPTIVE BEHAVIOR EVIDENCE FROMLABORATORY EXPERIMENT - Chytilova, Helena (European Scientific Journal, ESJ, 2013)
any studies deal with experimental investigation of rational behaviour, which might deviate from initial concepts under particular conditions, where subjects follow rather adaptive behaviour. The aim of this study is to verify whether adaptive behaviour might be prevalent in environment of nominal values characterized by uncertainty. Our hypothesis is verified with help of the experiment based on n-player pricing game with monopolistic competition and strategic complementarity inspired by experimental design of Fehr and Tyran, (2001), where players have to cope with environment of real or nominal values. Results confirm our initial assumption that in case of nominal treatment, subjects tend to behave rather in adaptive way, since the size of expectation correction is close to simulated case of adaptive player together with substantial deviation from equilibrium. On the other hand, subjects in the real treatment behave in less adaptive and even more rational way, where the size of expectation correction is far away from the case of adaptive player and deviation from equilibrium substantially smaller. Prevalence of adaptive players under the nominal treatment has also implications in terms of slower convergence to equilibrium at aggregate level, as opposed to the real treatment where more rational players are present. Furthermore, this is in line with our illustrative simulations carried out at economy´s level.